Multimodality evoked potentials for discrimination of atopic myelitis and multiple sclerosis. Issue 1 (16th May 2013) - Kanamori, Yuji; Isobe, Noriko; Yonekawa, Tomomi; Matsushita, Takuya; Shigeto, Hiroshi; Kawamura, Nobutoshi; Yamasaki, Ryo; Murai, Hiroyuki; Tobimatsu, Shozo; Kira, Jun‐ichi
Abstract Objectives To clarify the differences in multimodality evoked potential findings between patients with atopic myelitis (AM) and those with multiple sclerosis (MS). Methods A retrospective chart review of 70 consecutive AM patients and 93 MS patients was carried out. All patients were negative for serum anti‐aquaporin‐4 antibody. Visual‐ (VEP), somatosensory‐ (SEP) and motor‐evoked potentials (MEP) recorded at first examination, and magnetic resonance imaging (MRI) findings from the first examination were compared between AM and MS patients. Results Compared with MS patients, AM patients showed male preponderance, lower the Expanded Disability Status Scale scores and less frequent spinal cord MRI lesions. Visual impairment and muscle weakness were also less severe in AM patients. Frequencies of abnormal VEP and prolonged central conduction time on lower limb MEP were significantly lower in AM patients than in MS patients (AM vs MS: 9.5% vs 55.6%, and 28.2% vs 54.4%, respectively), whereas frequencies of peripheral nerve involvement in upper and lower limb MEP and upper limb SEP were significantly higher in AM than in MS patients (AM vs MS: 12.8% vs 2.9%, 17.9% vs 2.9% and 33.3% vs 4.4%, respectively). When patients whose EP were examined within 5 years of disease onset were compared, lower frequencies of abnormal VEP and higher peripheral nerve involvement detected by MEP and SEP were observed in AM patients. Conclusions AM patients have distinct physiological features compared with MS patients, even at the first examination of evoked potentials, which might suggest distinct immunological mechanisms between the two conditions. Multimodality evoked potentials might contribute to the early discrimination of these two disorders.